Efeitos da deleção do receptor mas na função cardiovascular de camundongos machos e fêmeas - Fernanda Brandão Machado Carneiro (2015)
Intrinsic sexual factors modulate the Renin Angiotensin System (RAS) determining lower blood pressure (BP) in women of reproductive age in comparison with men. Similar sex differences exist in rodents, in which females are more resistant to the development of hypertension. This protection found in females appears to be caused by a greater activation of the vasodilator axis of RAS, represented by Angiotensin-(1-7) [Ang-(1-7)] and its specific receptor, Mas. However, the real contribution of Ang-(1-7)/Mas for the physiological regulation of BP in each gender is not yet known. Therefore, we evaluated the effects of genetic Mas ablation on cardiovascular function, and the vasodilator effect of Ang-(1-7) in renal arteries of mice. BP of Mas-deficient (Mas−/−) and wild type (Mas+/+) mice was measured by telemetry. High-resolution echocardiography was performed and the Total peripheral resistance (TPR) and regional vascular resistance (VR) were measured by fluorescent microsphere infusion. The cardiac expression of extracellular matrix (EM) proteins, AT1 and AT2 receptors were assessed by western blotting. We also evaluated endothelial function in vivo and the ultrastructure of mesenteric artery by electron microscopy. The in vitro vasodilator response induced by Ang-(1-7) were assessed in renal interlobar arteries of male and female Mas+/+ mice using a small vessel myograph. The gene expression of RAS components was assessed by RTPCR and the Mas receptor expression by immunohistochemistry in renal vessels. Surprisingly, genetic Mas ablation caused opposite effects in BP of male (hypertension) and female (hypotension) mice. Decreased BP in female Mas−/− resulted from cardiac dysfunction and decreased RV in important organs such as kidneys, liver and skin. On the other hand, the increased BP found in males Mas−/− resulted from an increased deposition of EM in both, heart and arterial wall resulting in cardiac fibrosis, increased TPR and endothelial dysfunction. The fibrosis observed in the hearts of male Mas−/− resulted from higher expression of AT1 and increased activation of the ERK1/2 MAP kinase pathway. Other mechanisms appear to cause cardiac dysfunction in females Mas−/− since AT1 expression is reduced in their heart. Renal vessels from female mice presented increased Ang-(1-7) relaxation response, this effect was mediated by receptor Mas and resulted from higher NO bioavailability. Altogether, our data showed Ang-(1-7)/Mas modulates cardiac function and VR, supporting a critical role of this axis in sex-related differences in BP regulation. Although females show higher vasodilator response to Ang-(1-7) in vitro, genetic Mas ablation caused clearer effects on the cardiovascular system of male mice. These results reflect the importance of Ang-(1-7)/Mas for future therapeutic strategies for treating hypertension tailored according to the sex.